2021
DOI: 10.1016/j.amsu.2021.102731
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of immunohistochemical expression of HIF-1alpha and IDH1 with clinicopathological and therapeutic data of moroccan glioblastoma and survival analysis

Abstract: Introduction Glioblastomas are aggressive primary intracranial tumours of the central nervous system causing significant mortality and morbidity worldwide. Objective This study aims to evaluate the prognostic value of tissue expression by immunostaining of hypoxia-inducible factor (HIF-1α), isocitrate dehydrogenase 1 (IDH1), and tumour protein p53 in glioblastoma in Moroccan patients. The association of HIF-1α, IDH1, and p53 expression with the clinicopathological data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 43 publications
0
11
0
2
Order By: Relevance
“…Liu et al [28] study also found a significant difference of the HIF-1α expression and IDH1 mutation (p-value = 0.012). In grade 4 gliomas studied by Sfifou et al [23] most cases expressed HIF-1α (70%) were IDH1 R132H -ve.…”
Section: And [24] Respectively)mentioning
confidence: 88%
See 1 more Smart Citation
“…Liu et al [28] study also found a significant difference of the HIF-1α expression and IDH1 mutation (p-value = 0.012). In grade 4 gliomas studied by Sfifou et al [23] most cases expressed HIF-1α (70%) were IDH1 R132H -ve.…”
Section: And [24] Respectively)mentioning
confidence: 88%
“…The expression of HIF-1α indicates tumor hypoxia, which plays an essential role in initiation, progression and also therapy resistance. High HIF-1α is associated with bad prognosis in many tumors [23].…”
Section: Discussionmentioning
confidence: 99%
“…The group with "negative HIF-1α and positive IDH1" illustrated a better outcome with 85% survival rate at 12 months. Nevertheless, the patients with "positive HIF-1α and negative IDH1" expressed the worst prognosis with 18% survival [162].…”
Section: Ros and Hypoxiamentioning
confidence: 99%
“…In addition, hypoxia is a predominant feature involved in the development of the GBM microenvironment, considering its implication in the stability of HIF-1α. The latter is the hypoxia-inducible factor that has been identified as a major operator of the Warburg effect and the trigger in the occurrence of some solid tumors, including glioblastoma [162].…”
Section: Ros and Hypoxiamentioning
confidence: 99%
“…In GBM patients, more than half were p35 positive, and DNA sequencing analysis showed that p53-positive microvascular proliferating cells were identical to TP53 mutations observed in primary tumors. The p53 protein is encoded by the TP53 gene, which is thought to be the most mutated gene in human tumors 116 . The components of the deregulated p53 pathway are related to the invasion, migration, proliferation, avoidance of apoptosis and stem cell properties of GBM cells.…”
Section: Targets Of Gbm and Relevant Small-molecule Novel Therapeuticsmentioning
confidence: 99%